2014
DOI: 10.1186/1471-2202-15-97
|View full text |Cite
|
Sign up to set email alerts
|

Sleepiness induced by sleep-debt enhanced amygdala activity for subliminal signals of fear

Abstract: BackgroundEmotional information is frequently processed below the level of consciousness, where subcortical regions of the brain are thought to play an important role. In the absence of conscious visual experience, patients with visual cortex damage discriminate the valence of emotional expression. Even in healthy individuals, a subliminal mechanism can be utilized to compensate for a functional decline in visual cognition of various causes such as strong sleepiness. In this study, sleep deprivation was simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 45 publications
4
29
4
Order By: Relevance
“…Consistent with this view, we estimated less mediation for the quadratic effect of sleep duration on depression and anxiety risk in the university sample, suggesting the mediation effect in students is stronger for short sleep duration compared to long sleep. Sleep debt and daytime sleepiness can decrease certain behaviors (e.g., physical activity, leisure activities) (McAllister et al., ; McClain, Lewin, Laposky, Kahle, & Berrigan, ) and alter neurochemical (e.g., serotonin and norepinephrine) (Chellappa, Schroder, & Cajochen, ; Walker & van der Helm, ) and neuroanatomical processes (e.g., amygdala activity) (Motomura et al., , ) that accentuate negative emotions and increase psychopathology risk. Further research is needed to better understand the physiological and behavioral mechanisms underlying the interactions between sleep and mental health in different populations of young adults and other high‐risk groups (e.g., emergency personnel).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this view, we estimated less mediation for the quadratic effect of sleep duration on depression and anxiety risk in the university sample, suggesting the mediation effect in students is stronger for short sleep duration compared to long sleep. Sleep debt and daytime sleepiness can decrease certain behaviors (e.g., physical activity, leisure activities) (McAllister et al., ; McClain, Lewin, Laposky, Kahle, & Berrigan, ) and alter neurochemical (e.g., serotonin and norepinephrine) (Chellappa, Schroder, & Cajochen, ; Walker & van der Helm, ) and neuroanatomical processes (e.g., amygdala activity) (Motomura et al., , ) that accentuate negative emotions and increase psychopathology risk. Further research is needed to better understand the physiological and behavioral mechanisms underlying the interactions between sleep and mental health in different populations of young adults and other high‐risk groups (e.g., emergency personnel).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this view, we estimated less mediation for the quadratic effect of sleep duration on depression and anxiety risk in the university sample, suggesting the mediation effect in students is stronger for short sleep duration compared to long sleep. Sleep debt and daytime sleepiness can decrease certain behaviors (e.g., physical activity, leisure activities) (McAllister et al, 2009;McClain, Lewin, Laposky, Kahle, & Berrigan, 2014) and alter neurochemical (e.g., serotonin and norepinephrine) (Chellappa, Schroder, & Cajochen, 2009;Walker & van der Helm, 2009) and neuroanatomical processes (e.g., amygdala activity) (Motomura et al, 2013(Motomura et al, , 2014 Table S5 and Table S6). Social activity can also influence chronotype (Leonhard & Randler, 2009), and growing research suggests that the contribution of social relative to biological (circadian and sleep) factors on eveningness may vary in different social contexts (Natale, Adan, & Fabbri, 2009;Randler, Faßl, & Kalb, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The main aim of the study was to investigate the effects of sleep restriction on emotion regulation. It has previously been proposed that sleep deprivation causes increased amygdala activation in response to negative stimuli (6,40) and that the mechanism behind this phenomenon is a prefrontal-amygdala disconnect (6,41,42). We found no effect of sleep restriction on amygdala activity nor connectivity to negative stimuli for passive viewing.…”
Section: Discussionmentioning
confidence: 99%
“…A recent fMRI study has further shown that the sleep debt accrued by prolonged sleep restriction can produce a similar hyper-responsivity of the amygdala to emotional faces as well as reduce its functional connectivity with the vmPFC (ventral anterior cingulate) (Motomura et al, 2013). Additionally, these same investigators showed that sleep-debt induced amygdala hyperactivity also extends to subliminally presented (backward masked) emotional-face stimuli (Motomura et al, 2014). In addition to increased reactivity of neural structures to negative stimuli, TSD has also been shown to increase the reactivity of the mesolimbic reward system to positive stimuli as well as decrease its functional connectivity with regulatory prefrontal regions suggesting that the emotional regulatory function of sleep may be important in a bivalent manner (Gujar, Yoo, Hu, & Walker, 2011).…”
Section: Sleep and Emotional Declarative Memorymentioning
confidence: 99%